2011
DOI: 10.1007/s00170-011-3669-8
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic vibration-assisted optical glass hot embossing process

Abstract: A homemade apparatus was used to apply ultrasonic-vibration to assist the glass hot embossing processes. To operate at high temperatures for glass hot embossing, the ultrasonic vibration system was appropriately designed with an embedded cooling system, and an ultrasonic horn was specifically modified for hightemperature use. Molds with both V-groove and Fresnel structures were manufactured for hot embossing experiments on PSK-100 glass. The heights of the molded structures were increased significantly with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…In hot embossing process, ultrasonic vibration caused an increase of local temperature between the molds and materials, enabling the softening materials to easily fill in the mold cavities. Forming forces decreased rapidly owing to the softened materials, evidencing that ultrasonic vibration could improve the forming performance of hot embossing process [30,31]. Similarly, the findings in extrusion process have shown that the applied ultrasonic vibration could also reduce the extrusion force and material flow stress by decreasing the friction force between the die and materials [32].…”
Section: Uv-a Forming Processesmentioning
confidence: 88%
“…In hot embossing process, ultrasonic vibration caused an increase of local temperature between the molds and materials, enabling the softening materials to easily fill in the mold cavities. Forming forces decreased rapidly owing to the softened materials, evidencing that ultrasonic vibration could improve the forming performance of hot embossing process [30,31]. Similarly, the findings in extrusion process have shown that the applied ultrasonic vibration could also reduce the extrusion force and material flow stress by decreasing the friction force between the die and materials [32].…”
Section: Uv-a Forming Processesmentioning
confidence: 88%
“…Studies have reported that ultrasonic vibration yields beneficial effects. 7 Tsai et al 8 recently conducted hot embossing experiments to examine the effect of ultrasonic vibration on glass micro-replication. 5 In addition, ultrasonic vibration-assisted forming processes have recently been conducted using amorphous materials such as polymers, composites, and glasses.…”
Section: Ultrasonic Vibration-assisted Hot Glass Embossing Processmentioning
confidence: 99%
“…In addition, ultrasonic vibration can increase the filling efficiency of polymers during ultrasonic nanoimprint lithography. 7 Tsai et al 8 recently conducted hot embossing experiments to examine the effect of ultrasonic vibration on glass micro-replication. Furthermore, Hung et al 9 reported that embossing forces reduced markedly when applying the ultrasonic vibrationassisted hot glass embossing process.…”
Section: Ultrasonic Vibration-assisted Hot Glass Embossing Processmentioning
confidence: 99%
“…When forming glass elements with sharp‐cornered microstructures, however, incomplete filling and excessive stress of the glass are of common occurrence as its rheological behavior is distinctly restricted in microscale mold cavities, which lead to geometric and optical defects of the final products . In light of such technical bottlenecks, researchers have recently developed some ultrasonic‐involved molding techniques for fabricating microstructures with higher accuracies . Differing from ultrasonic‐assisted imprinting process for polymers, great technical challenges arise in ultrasonic‐assisted glass molding process (UGMP) due to the much higher molding temperature required for glasses.…”
Section: Introductionmentioning
confidence: 99%
“…Tsai and Hung might be the first to develop an apparatus specially for forming glass with ultrasonic vibrations, with which they conducted hot pressing tests for both microgrooves and Fresnel lens of glass K‐PSK100. The experimental results revealed the great potential of the ultrasonic vibration to fabricate high‐precision microstructures, while relevant mechanisms remained to be explored . Later on, Nguyen et al investigated the ultrasonic vibration‐assisted hot embossing process on the basis of the ultrasonic thermal effect.…”
Section: Introductionmentioning
confidence: 99%